Hospitalisations related to administration errors of psychotropic drugs: a nationwide retrospective study between 1998 and 2019 in Australia - Alsaleh, Fatemah M.; Naser, Abdallah Y.; Alsairafi, Zahra K.; Ofori-Asenso, Richard (Frontiers in Pharmacology, 2023)
Objectives: Medication administration error occurs when there is a discrepancy between what the patient received or was planned to receive and what the doctor originally intended. The aim of this study was to examine the trends in hospitalisation related to administration errors of psychotropic drugs in Australia.This was a secular trend analysis study that examined the hospitalisation pattern for medication administration errors of psychotropic drugs in Australia between 1998 and 2019. Data on medication administration errors of psychotropic drugs was obtained from The National Hospital Morbidity Database. We analysed the variation in hospitalisation rates using the Pearson chi-square test for independence.Results: Hospitalisation rates related to administration errors of psychotropic drugs increased by 8.3% [from 36.22 (95% CI 35.36 -37.08) in 1998 to 39.21 (95% CI 38.44 -39.98) in 2019 per 100,000 persons, p<0.05]. Overnight-stay hospital admission patients accounted for 70.3% of the total number of episodes. Rates of same-day hospitalisation increased by 12.